Geomorphological Diversity and Habitat Variability. A Model of Late Palaeolithic Catchment Composition in Northern Bavaria - Sauer, Florian; Uthmeier, Thorsten (Quartär. International Yearbook for Ice Age and Stone Age Research, 2020)
Due to the lack of adequate data, the environmental and bioeconomic framework of archaeological sites often cannot be investigated. This situation is visible with the Late Palaeolithic in Southern Germany, which is typically represented by surface collections that do not provide ecological information. In this paper, we analyse the topographic composition of site-catchments of Late Palaeolithic sites in Northern Bavaria (Germany). We use a geomorphology-driven approach, which employs the close relationship between local topography and abiotic conditions relevant to plant growth. This way it is possible to model potential regional physiotope diversity and habitat patterning. This methodology allows the analysis of site-environment relationships in cases, when traditional proxies, like palynological or faunal data are lacking or do not provide an adequate spatial extent and resolution. In this paper, site catchment analysis and physiotope diversity estimation for Late Palaeolithic sites in the study area highlight the relevance of relatively specialized landscapes, which provide comparably wet conditions. This indicates the focus of Late Glacial foragers on the exploitation on bioresources associated with wetland and floodplain environments in the study area.
CRIS-Team Scopus Importer:2024-12-16
Keywords: biodiversity; catchment analysis; environmental modelling; geomorphology; land use pattern; Late Palaeolithic